Arts-Based Inquiry and Teacher Reflection: a Teacher Institute (LAEL, PUC-SP) - Diamond, C. T. Patrick (The ESPecialist, 2012)
A three-week Teacher Education and Reflection Institute (TERI97) was trialled at LAEL, Pontifícia Universidade Católica de São Paulo (PUC-SP) in 1997. This Institute was designed around principles specific to qualitative arts-based inquiry and teacher development. The textual, allegorical strategies that were used to raise teachers’ conscious awareness of self-practice included: professional self-characterizations; sorting these different aspects of teacher self; mapping the development of a teaching career (extensively using timelines and intensively using river roads or snake trails); and subject autobiographies and metaphor-making. These activities and questions enabled teachers to reflect upon the teacher I am, the teacher I hope to become, and the teacher I fear to be as crucial aspects of a developing teacher self. Construing development as self-multiplication allowed both charges of narcissism and inadequacy (the inner critic) to be answered. By looking at ourselves as teachers in the act of looking, we acquire second sight. As teacher inquirers, we are obliged to self-reflect, since by looking at ourselves we come to know our teaching in new ways.